Strategy Making in Nonprofit Organizations - Vradelis, Mary (Business Expert Press, 2012)
Ebook from IG Library ; Nonprofit Organizations need strategies to be effective, but the available tools for making strategy were developed primarily for business organizations. This book provides a model and several case studies for Strategy Making in Nonprofit Organizations. The strategy making model modifies the business practices of Strategy-Structure-Systems for the nonprofit context with a focus on Purpose-Processes-People that is more suitable to meet their unique challenges. In this book, the leaders of nonprofit organizations will find ways to better articulate the challenges that their organizations face for communicating with their business partners, donors and employees. As the demand for essential social services is growing and the budgets are declining, leaders and managers in both Nonprofit and Business organizations need the solutions offered in this book. Nonprofit Organizations face an external environment where demand outstrips their ability to meet it. They face competition in raising funds and resources to provide these services. They rely on processes to harness the creativity of their people in delivering to the triple bottom line of economic, social and environmental impact. This book provides a bridge between business and nonprofit organizations.